Analysis of Factors Influencing Consumer Behavior on Plant-Based Foods Products through Theory of Planned Behavior and Green Marketing Approach - Wirahadi Saputra; Lamhot Henry Pasaribu (Budapest International Research and Critics University, 2023)
Plant-based foods in Indonesia have become a concern in recent years. This study explores the factors that influence consumer intentions and behavior towards plant-based food products in Indonesia by conducting an empirical study on Green Rebel, one of the brand and manufacturer of plant-based foods in Indonesia. The conceptual model used in this study uses the standard theory of planned behavior model. This study adds the green marketing variable as a new variable in addition to the relationship between attitudes, subjective norms, and perceptions of behavioral control, intentions and behavior so that there is a novelty in this study. Behavioral intention is expected to mediate the relationship with actual behavior. This research was conducted on consumers of plant-based foods from Green Rebel with a total of 173 research subjects. Data analysis was performed using the partial least square quation model (PLS-SEM) method and analyzed using Smart PLS 4.0 software. The results of the study show that attitudes positively influence behavioral intentions, as well as subjective norms, perceived behavioral control, and green marketing. The results also show that intention mediates the relationship between attitudes, subjective norms, behavior control, and green marketing with actual behavior. Green marketing directly has an influence on behavior without the need to be mediated by intention.